The role of radiological interventions in hepatocellular carcinoma before liver transplantation: a surgical perspective - Alim, Altan; DuBay, Derek (Frontiers in Surgery, 2025)
Liver transplantation (LT) remains the gold standard treatment for patients with unresectable hepatocellular carcinoma (HCC) within or, in select cases, beyond the Milan criteria. However, with the increasing complexity of HCC management and the scarcity of donor organs, the role of liver directed therapies have gained prominence in optimizing patient outcomes. Downstaging therapies and bridging therapies have become essential components of HCC management. This review explores the pivotal role of interventional radiology interventions, including thermal ablation techniques (radiofrequency ablation, microwave ablation) and transarterial therapies (transarterial chemoembolization, transarterial radioembolization), in the pre-transplantation setting. These therapies not only improve LT eligibility for patients exceeding traditional tumor criteria but also enhance survival by maintaining disease control and reducing dropout rates from the LT waiting list. The review further discusses the complexities of patient selection, contraindications, and the evolving strategies in locoregional therapy to maximize LT outcomes. Liver directed therapies, through both downstaging and bridging, are integral to managing HCC, offering significant benefits in post-transplant survival, while ensuring that LT is conducted based on appropriate indications.